The California Environmental Flows Framework: Meeting the Challenges of Developing a Large-Scale Environmental Flows Program - Stein, Eric D.; Zimmerman, Julie; Yarnell, Sarah M.; Stanford, Bronwen; Lane, Belize; Taniguchi-Quan, Kristine T.; Obester, Alyssa; Grantham, Theodore E.; Lusardi, Robert A.; Sandoval-Solis, Samuel (Frontiers in Environmental Science, 2021)
Environmental flow programs aim to protect aquatic habitats and species while recognizing competing water demands. Often this is done at the local or watershed level because it is relatively easier to address technical and implementation challenges at these scales. However, a consequence of this approach is that ecological flow criteria are developed for only a few areas as dictated by funding and interest with many streams neglected. Here we discuss the collaborative development of the California Environmental Flows Framework (CEFF) as an example process for developing environmental flow recommendations at a statewide scale. CEFF uses a functional flows approach, which focuses on protecting a broad suite of ecological, geomorphic, and biogeochemical functions instead of specific species or habitats, and can be applied consistently across diverse stream types and spatial scales. CEFF adopts a tiered approach in which statewide models are used to establish ecological flow needs based on natural functional flow ranges, i.e., metrics that quantify the required magnitude, timing, duration, frequency, and/or rate-of-change of functional flow components under reference hydrologic conditions, for every stream reach in the state. Initial flow needs can then be revised at regional, or watershed scales based on local constraints, management objectives, and available data and resources. The third tier of CEFF provides a process for considering non-ecological flow needs to produce a final set of environmental flow recommendations that aim to balance water needs of all desired uses. CEFF was developed via a broad inclusive process that included technical experts across multiple disciplines, representatives from federal and state agencies, and stakeholders and potential end-users from across the state. The resulting framework is therefore not associated with any single agency or regulatory program but can be applied under different contexts, mandates and end-user priorities. The inclusive development approach also allowed us to achieve consensus on the technical foundations and commitment to applying this approach in the future.